Cluster, a potential tool for rural development - Micskei, Péter (Acta Agraria Debreceniensis, 2012)
There was a heavy change in the characteristics of the agriculture in the last 20 years. It become a multifunctional, sustainable, organic system, which needs strategic approach. On the problem map of the hungarian agriculture the most importatnt questions are the following: dual charachter of the land structure, to occidentalize the farm structure. To develop the rural areas we need to real markets needs adapted, competitive, local agricultural production. From the ’90s into Europe’s economic development policies integrated the clusters, this research tries to certify, that this system is viable in classic agriculture and able to dissolve the defecinces, to support the aims of rural development.